Ammonia removal and nitrogen preferences evaluation of indigenous Malaysian microalga Halamphora sp. on white shrimp Penaeus vannamei wastewater - Ghazali, Nurarina Ayuni; Abdul Halim, Nurul Aini; Baharuddin, Ninie Diana; Md. Yusoff, Fatimah; Karim, Murni; Natrah, Ikhsan (Genesis Publishing Consortium Limited, 2024)
Ammonia is ubiquitous in aquaculture systems and its removal is important for maintaining water quality and the health of the cultured animals. Microalgae are effective at removing ammonia from water, but the effectiveness of different microalgae species may vary. In this study, indigenous Malaysian microalgae isolated from shrimp ponds were screened for their ability in removing ammonia from synthetic culture media. The most efficient microalga’s nitrogen preferences and its growth and nitrogen removal in the early and late stages of shrimp culture wastewater were explored. It was found that four microalgae species namely Halamphora sp. BpSpD2, Chaetoceros sp. BpSpD3, Chlorella sp. BpSpG3 and Desertifilum sp. BpSpC1 were able to eradicate ammonia after 14 days of cultivation. Further investigation showed that Halamphora sp. BpSpD2 was able to remove 100 % ammonia within 5 days of culture. The nitrogen preferences of Halamphora sp. BpSpD2 indicated a preference for ammonia over nitrate as evidenced by the higher growth and removal efficiency of the treatments. Nitrogen removal efficiency of over 70 % was observed in treating 4 to 12 mg L-1 of TAN and nitrate. When tested in shrimp-cultured wastewater, Halamphora sp. showed a higher growth and 100% ammonia removal efficiency in the late stage of shrimp-culture wastewater. It also effectively removed 59% to 80% of nitrogen throughout both the early and late stages of shrimp culture wastewater. The results suggested that the microalga Halamphora sp. BpSpD2 has a significant potential to treat the effluent of an aquaculture system containing high concentrations of ammonia and nitrate.